2019
DOI: 10.1111/ggr.12256
|View full text |Cite
|
Sign up to set email alerts
|

High‐Precision Barium Isotope Measurements of Carbonates by MCICPMS

Abstract: This study presents a high‐precision method to measure barium (Ba) isotope compositions of international carbonate reference materials and natural carbonates. Barium was purified using chromatographic columns filled with cation exchange resin (AG50W‐X12, 200–400 mesh). Barium isotopes were measured by MC‐ICP‐MS, using a 135Ba–136Ba double‐spike to correct mass‐dependent fractionation during purification and instrumental measurement. The precision and accuracy were monitored by measuring Ba isotope compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…The average δ 137/134 Ba values in bulk rock of basalts (BHVO-2 and JB-2) were 0.04 ± 0.02‰ and 0.07 ± 0.03‰. Our obtained Ba isotope compositions in these reference materials are in a good agreement with previously reported values by Nan et al 11 and Miyazaki et al 24 Our carbonatite COQ-1 bulk rock analysis (δ 137/134 Ba = 0.06 ± 0.02‰) is also in a good agreement with that of 0.08 ± 0.04‰ by Zeng et al 26 As a result, the distribution of δ 137/134 Ba in standard reference materials and geological samples is illustrated in Figure 3. A plot of δ 138/134 Ba vs δ 137/134 Ba among selected geological samples and standard reference materials by the DS-TIMS approach is given in Figure 4, implying the barium isotopes in geological reference materials, as well as the in-house reference materials, follow the mass-dependence fractionation Line (MDFL), which is in agreement with the calculations by Young.…”
Section: ■ Experimental Sectionsupporting
confidence: 92%
See 2 more Smart Citations
“…The average δ 137/134 Ba values in bulk rock of basalts (BHVO-2 and JB-2) were 0.04 ± 0.02‰ and 0.07 ± 0.03‰. Our obtained Ba isotope compositions in these reference materials are in a good agreement with previously reported values by Nan et al 11 and Miyazaki et al 24 Our carbonatite COQ-1 bulk rock analysis (δ 137/134 Ba = 0.06 ± 0.02‰) is also in a good agreement with that of 0.08 ± 0.04‰ by Zeng et al 26 As a result, the distribution of δ 137/134 Ba in standard reference materials and geological samples is illustrated in Figure 3. A plot of δ 138/134 Ba vs δ 137/134 Ba among selected geological samples and standard reference materials by the DS-TIMS approach is given in Figure 4, implying the barium isotopes in geological reference materials, as well as the in-house reference materials, follow the mass-dependence fractionation Line (MDFL), which is in agreement with the calculations by Young.…”
Section: ■ Experimental Sectionsupporting
confidence: 92%
“…The isotopic compositions of dissolved Ba in seawater and river samples with a long-term reproducibility of ±0.03‰ (2SD), suggested that the proxy can be used as a new tracer for weathering processes and coastal water mass mixing. 12 Accurate Ba isotopes measurements in corals, stalagmite and Barite have been achieved with an external reproducibility better than ±0.03‰ (2SD) by Liu, 25 Zeng, 26 and Tian. 27 Compared to the approach with MC-ICP-MS analysis which can be affected by inherent isobaric interferences from the carrier gas (e.g., 130,132,134 Xe), and impurities in solution such as rare earth elements (e.g., 136 La, 138 La, 138 Ce) and polyatomic ions (e.g., ZrAr + (m/z = 132, 134, 136), MoAr + (m/z = 130, 132, 134, 136, 138)), the TIMS technique, in combination with the double spike method ensures high quality barium isotope measurement.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Ba isotope compositions in coral and seawater are reported in the δ‐notation (‰) relative to the value of the National Institute of Standards and Technology (NIST) Ba Standard Reference Material 3104a based on the formula: δ 138/134 Ba = [( 138 Ba/ 134 Ba sample )/( 138 Ba/ 134 Ba SRM 3104a ) – 1] × 1,000. Repeat analysis of the coral standard JCp‐1 and YXI‐USTC from the Yongxing Island yielded mean δ 138/134 Ba values of 0.31 ± 0.03‰ and 0.36 ± 0.02‰, respectively, consistent with the respective certified values of 0.29 ± 0.03‰ (Horner et al., 2015) and 0.36 ± 0.04‰ (Zeng et al., 2019). The reproducibility of the seawater δ 138/134 Ba measurements was ±0.06‰ (Cao, Li, et al., 2020).…”
Section: Methodssupporting
confidence: 71%
“…[Ba] sw values were analyzed using isotope dilution ICP‐MS at the State Key Laboratory of Marine Environmental Science of Xiamen University, Xiamen, China (Cao, Li, et al., 2020). Analyses of Ba isotopes in coral and seawater were conducted on the multicollector ICP‐MS (MC‐ICP‐MS) at the CAS Key Laboratory of Crust‐Mantle and Environments at the University of Science and Technology of China, Hefei, China (Zeng et al., 2019), and a Nu Plasma HR MC‐ICP‐MS at the State Key Laboratory of Marine Environmental Science of Xiamen University, Xiamen, China (Cao, Li, et al., 2020), respectively. Ba isotope compositions in coral and seawater are reported in the δ‐notation (‰) relative to the value of the National Institute of Standards and Technology (NIST) Ba Standard Reference Material 3104a based on the formula: δ 138/134 Ba = [( 138 Ba/ 134 Ba sample )/( 138 Ba/ 134 Ba SRM 3104a ) – 1] × 1,000.…”
Section: Methodsmentioning
confidence: 99%